2009
DOI: 10.1037/a0016366
|View full text |Cite
|
Sign up to set email alerts
|

Does devoutness delay death? Psychological investment in religion and its association with longevity in the Terman sample.

Abstract: Religious people tend to live slightly longer lives (M. E. McCullough, W. T. Hoyt, D. B. Larson, H. G. Koenig, & C. E. Thoresen, 2000). On the basis of the principle of social investment (J. Lodi-Smith & B. W. Roberts, 2007), the authors sought to clarify this phenomenon with a study of religion and longevity that (a) incorporated measures of psychological religious commitment; (b) considered religious change over the life course; and (c) examined 19 measures of personality traits, social ties, health behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 67 publications
(112 reference statements)
2
19
0
1
Order By: Relevance
“…These findings illustrate the importance of examining multiple dimensions of religious involvement as related to health outcomes. They also mirror previous research showing that women are more religiously involved than men [35,36] and that there are sex differences in religion's role in health behaviors and outcomes [37][38][39][40][41]. Somewhat puzzling is the finding that religious denomination plays a more complex role in risky sexual behaviors for men than for women.…”
Section: Discussionsupporting
confidence: 80%
“…These findings illustrate the importance of examining multiple dimensions of religious involvement as related to health outcomes. They also mirror previous research showing that women are more religiously involved than men [35,36] and that there are sex differences in religion's role in health behaviors and outcomes [37][38][39][40][41]. Somewhat puzzling is the finding that religious denomination plays a more complex role in risky sexual behaviors for men than for women.…”
Section: Discussionsupporting
confidence: 80%
“…Ample experimental evidence documents the association between religious participation and mortality, where religious individuals live longer than do their non-religious counterparts (e.g., McCullough, Friedman, Enders, & Martin, 2009). For example, Hummer, Rogers, Nam, and Ellison (1999) have shown that Americans who attend worship services twice a week live an average of 7.6 years longer than their non-attending counterparts (a figure that nearly doubles to 13.7 years among African Americans; see Marks et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…For example, church attendance has been associated with a positive perception of health among older adults with chronic diseases (Yohannes, Koenig, Baldwin, & Connolly, 2008), increased physical functioning (Koenig, George, & Titus, 2004), and less co-morbidity (Koenig et al, 2004;Yohannes et al, 2008). Religious participation also has been linked to lower rates of depression (Cruz et al, 2009), lower mortality rates (McCullough, Hoyt, Larson, Koenig, & Thoresen, 2000;Powell, Shahabi, & Thoresen, 2003), and increased longevity (Gartner, Larson, & Allen, 1991;McCullough, Friedman, Enders, & Martin, 2009;Yohannes et al, 2008). Though functional limitations are more likely to hinder their attendance at religious services compared to younger individuals (Benjamins & Finlayson, 2007), older adults are more likely to engage in prayer, attend church, and derive greater life satisfaction from their religious practices (Fiori et al, 2006; see also Krause, 2004, for review).…”
Section: Religious Participation and Well-beingmentioning
confidence: 99%